Exploring osteosarcopenia from the gut microbiota perspective: mechanistic insights and therapeutic potentials based on the gut-muscle-bone Axis - Jiang, Hao-bo; Zhang, Jun-qi; Liang, Hao; Sun, Li-ying; Deng, Chang-qing; Yang, Shao-feng (Frontiers in Microbiology, 2026)
The aging society presents a growing challenge in the form of osteosarcopenia (OS). This syndrome is marked by the concomitant deterioration of bone (osteoporosis) and muscle (sarcopenia), and significantly elevates the risks of fractures, disability, and mortality. Despite its clinical relevance, the shared pathophysiology and effective interventions for OS remain elusive. Emerging evidence highlights the gut microbiota (GM) as a critical modulator of musculoskeletal health. This review integrates current evidence to delineate “gut-muscle-bone Axis” framework, summarizing current evidence on how GM dysbiosis may be involved in OS through multifaceted mechanisms, including intestinal barrier disruption, chronic inflammation, endocrine dysregulation, impaired nutrient absorption, and disrupted muscle-bone crosstalk. GM-derived metabolites, such as short-chain fatty acids (SCFAs), interact with immune, metabolic, and hormonal pathways to influence osteoblast/osteoclast activity and muscle protein synthesis. Furthermore, systemic inflammation triggered by GM imbalance exacerbates bone resorption and muscle atrophy. The axis also highlights bidirectional feedback between muscle and bone, mediated by myokines (e.g., irisin) and osteokines (e.g., osteocalcin), which synergistically regulate musculoskeletal homeostasis. Therapeutic strategies targeting GM modulation—such as dietary optimization (plant-based proteins, high-fiber diets), probiotics/prebiotics, exercise, and fecal microbiota transplantation (FMT)—suggest a potential capacity to modulate gut–muscle–bone interactions, which may be relevant to osteosarcopenia-related pathophysiological processes. This review proposes an integrative conceptual framework for understanding the pathogenesis of OS, synthesizing evidence primarily derived from osteoporosis and sarcopenia research, as well as animal and mechanistic studies. While direct clinical evidence in OS remains limited, emerging findings suggest that microbiota-centered strategies may hold potential for future preventive and therapeutic exploration.